Evaluating Public Service Quality: Why Employee Performance Outshines Service Standards and Work Culture in Shaping User Satisfaction - Fadly Achmad; Dwi Putranto Riau; Tora Akadira (Al-Qalam Institute, 2025)
This study aims to analyze the relationships among service standards, work culture, and employee performance in customer satisfaction in public services. A quantitative associative approach was employed, using Structural Equation Modeling (SEM) with SmartPLS 3.0 for data analysis. The study involved 70 institutions representing the entire population of service users. The results indicate that service standards and work culture have positive but not statistically significant effects on customer satisfaction, whereas employee performance has a positive, statistically significant effect. Simultaneously, service standards, work culture, and employee performance have a moderate positive influence on customer satisfaction. These findings imply that improving employee performance should be prioritized to enhance customer satisfaction. At the same time, service standards and work culture need to be strengthened through more effective implementation and organizational development strategies. Strengthening these aspects can support better service quality and increase overall user satisfaction in public services.